Optimasi Jangkauan Detektor Api Nirkabel Untuk Sistem Peringatan Dini Kebakaran - Nofri Afandi; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Fire is one of the most common disasters. It causes a lot of collateral damages annually. Not just material damages, casualties also took place frequently. In accordance to deter, there’s a lot of challenge faced, for example the difficulties of finding the source of fire as early as possible, that let the fire continue to spread easily. This research attempts to examine how to anticipate the occurrence of a fire that requires a device that works automatically and can detect early and minimize the possibility of widespread fire. Therefore, a tool was designed to prevent all losses cause by fire. One of them is by utilizing early warning system. Device are built using the HC-12 module as the sender and receiver of serial data through the air media. As the test result, it was known that HC-12 module can transmit and receive data in distance reaching 200 – 1300 m. .Keyword : HC-12 Transceiver Module, Arduino Pro Mini, Temperature Sensor LM35